Gender-specific strategy use and neural correlates in a spatial perspective taking task - Kaiser, Stefan; Walther, Stephan; Nennig, Ernst; Kronmüller, Klaus-Thomas; Mundt, Christoph; Weisbrod, Matthias; Stippich, Christoph; Vogeley, Kai (Neuropsychologia, 2008)
In the context of the present study spatial perspective taking refers to the ability to translocate one's own egocentric viewpoint to somebody else's viewpoint in space. We adopted a spatial perspective taking paradigm and performed a functional magnetic resonance imaging study to assess gender differences of neural activity during perspective taking. 24 healthy subjects (12 male/12 female) were asked to systematically either take their own (first-person-perspective, 1PP) or another person's perspective (third-person-perspective, 3PP). Presented stimuli consisted of a virtual scenery with an avatar and red balls around him that had to be counted, if visible, from 1PP or 3PP. Reaction time was increased and correctness scores were decreased during the cognitively more effortful 3PP condition. Correctness scores showed a trend towards a more pronounced decline of performance during 3PP as compared to 1PP in female subjects. Female subjects correctness scores declined by 6.7% from 1PP to 3PP, while in male subjects this performance decline was only 2.7%. Debriefings after the experiment, reaction times depending on angle of rotation and error rates suggest that males are more likely to employ an object-based strategy in contrast to a consistently employed egocentric perspective transformation in females. In the whole group, neural activity was increased in the parieto-occipital, right inferior frontal and supplementary motor areas, confirming previous studies. With respect to gender, male subjects showed stronger activation in the precuneus and the right inferior frontal gyrus than female subjects in a region-of-interest approach. In a subgroup of male subjects whose strategy reports suggest object-based strategies these differences seem to be more pronounced. In conclusion, the differential recruitment of brain regions most likely reflects different strategies in solving this spatial perspective taking task.
Gesehen am 22.11.2021